2009
DOI: 10.1016/j.ydbio.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of zebrafish cerebellum and screen for mutations affecting its development

Abstract: The cerebellum is important for the integration of sensory perception and motor control, but its structure has mostly been studied in mammals. Here, we describe the cell types and neural tracts of the adult zebrafish cerebellum using molecular markers and transgenic lines. Cerebellar neurons are categorized to two major groups: GABAergic and glutamatergic neurons. The Purkinje cells, which are GABAergic neurons, express parvalbumin7, carbonic anhydrase 8, and aldolase C like (zebrin II). The glutamatergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
501
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(529 citation statements)
references
References 112 publications
24
501
1
3
Order By: Relevance
“…Most of the other Tg(olig2:EGFP) cells were suggested to be neurons as they express the neuronal marker HuC/D and not Sox10 (Bae et al, 2009). This is in contrast to our results in the telencephalon where we could not detect co-expression of HuC/ D and Tg(olig2:EGFP).…”
Section: Olig2 Cells In the Parenchyma Of The Telencephaloncontrasting
confidence: 99%
See 1 more Smart Citation
“…Most of the other Tg(olig2:EGFP) cells were suggested to be neurons as they express the neuronal marker HuC/D and not Sox10 (Bae et al, 2009). This is in contrast to our results in the telencephalon where we could not detect co-expression of HuC/ D and Tg(olig2:EGFP).…”
Section: Olig2 Cells In the Parenchyma Of The Telencephaloncontrasting
confidence: 99%
“…Precedent studies of olig2 expression in a different adult zebrafish brain region, the cerebellum, showed that only a minority of Tg(olig2:EGFP) cells co-express Sox10 (Bae et al, 2009). Most of the other Tg(olig2:EGFP) cells were suggested to be neurons as they express the neuronal marker HuC/D and not Sox10 (Bae et al, 2009).…”
Section: Olig2 Cells In the Parenchyma Of The Telencephalonmentioning
confidence: 99%
“…Because the connectivity of the cerebellum in teleost fish is similar to that in mammals (Bae et al, 2009) and some reports have suggested its involvement in learning (Gó mez et al, 2010), we hypothesized that the zebrafish cerebellum plays a similar role in our simple conditioning protocol. We found that CCe lesions delivered before conditioning prevented the acquisition of the CR, whereas memory retention and expression remained unaffected when the cerebellum was ablated after conditioning (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…An overview of mglur expressions in larval zebrafish is shown in Table 2. We generally followed the nomenclature of the zebrafish brain atlas of larval (Mueller and Wullimann, 2005) and adult (Wullimann et al, 1996) zebrafish and followed some modifications suggested by other authors (Bae et al, 2009;Wullimann and Mueller, 2004a;Mueller et al, 2006 is located in Purkinje cells but additionally in the granule cell layer of the corpus cerebelli and in the lobus caudalis cerebelli (GCL, LCa; Fig. 4L,R-T).…”
Section: Distinct Expression Patterns For Mglurs In the Larval And Admentioning
confidence: 99%
“…Consistent with that we find prominent expression for both mglur1 paralogs in the zebrafish cerebellum. At larval stages the cerebellar mglur1a-riboprobe detects cells that resemble a Purkinje cell staining of an antibody against Parvalbumin7 (Bae et al, 2009). In contrast to Parvalbumin 7, mglur1b is additionally expressed in a subpopulation of granule cells in the dorsal and lateral part of the cerebellum.…”
Section: Cerebellummentioning
confidence: 99%